Renovation part 1: assessing the damage - Mortland, Karen K; Mortland, Daniel B (Clinical leadership & management review, 2004)
Once a general analysis of existing conditions is complete, a clearer picture of renovation costs and feasibility should emerge. This may be a point of renegotiation with owners. If the assigned space proves unsuitable in layout or requires budget busting upgrades to utilities, you may, now equipped with the results of your fact finding developed in concert with third party professionals, revisit the subjects of location and budget with owners. If, on the other hand, your survey reveals that you have indeed discovered a good foundation for renovation that fits the budget, it's time to swallow that lump in your throat and proceed.